Studies About The Effect of Different Photosynthetic Light Intensity On Two Isolated Species of Marine Microalgae (Diatom) for High Lipid Production - Jayakumar, Saravanan; Liang, Yan Peng; Mohd Hasbi, Ab. Rahim; Gaanty Pragas, Maniam (AENSI Publisher, 2015)
Diatoms are very photosensitive and well known for their changes of direction in different light conditions. The light energy is detected by diatom at the apex of the cell. Diatom needs light energy to manufacture food and increase the cell density for itself. Objective: In this study, we tested the influence of four different light intensities on the batch cultures of two diatom species. The growth rate, dry cell weight and chlorophyll a were correlated with lipid accumulation for biodiesel production. Results: The growth rates of Amphora sp. and Gyrosigma sp. both recorded the highest point for the highest light intensity ( 40 μmo! m·2s· 1) which are 0.2860 d-1 and 0.3067 d-1 respectively. The highest dry cell weight resulted using the highest light intensity as well where both documented 0.1354 g and 0.1683 g. At the highest light intensity, the chlorophyll a reading were 0.1779 ± 0.0059 and 0.1744 ± 0.0133. Conclusion: In short, the strength of light energy is believed to influence the growth of microalgae, chlorophyll a, microalgal biomass and its lipid content for biodiesel production purposes.